MENINGKATKAN HASIL BELAJAR SISWA MENGGUNAKAN METODE SIMULASI PADA MATA PELAJARAN BAHASA INDONESIA KELAS III MI MA’ARIF NU 6 KARYAMUKTI: MENINGKATKAN HASIL BELAJAR SISWA MENGGUNAKAN METODE SIMULASI PADA MATA PELAJARAN BAHASA INDONESIA KELAS III MI MA’ARIF NU 6 KARYAMUKTI - Novita Sari; Nurkaif; Sulis Anjarwati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Indonesian language learning in Grade III at MI Ma’arif NU 6 Karyamukti still shows low learning outcomes due to a lack of student involvement and the use of conventional teaching methods. Therefore, an active and appropriate learning method is required, one of which is the simulation method. This study aims to improve student learning outcomes in Indonesian language subjects through the simulation method in Grade III at MI Ma’arif NU 6 Karyamukti.This research employs the Classroom Action Research (CAR) method, conducted in two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. The subjects of this study were 17 students of Grade III at MI Ma’arif NU 6 Karyamukti. Data collection techniques were conducted through observation, interviews, learning outcome tests, and documentation. Data analysis used a mixed-method approach. The results indicated that the simulation method can improve Indonesian language learning outcomes for Grade III at MI Ma’arif NU 6 Karyamukti. Initial data obtained from students' daily test scores showed a completion rate of only 35%. This increased to 71% in Cycle I and experienced a significant improvement to 88% in Cycle II. Based on this research, it can be concluded that the simulation method is effective in improving student learning outcomes in Indonesian language subjects for Grade III at MI Ma’arif NU 6 Karyamukti.